2012
DOI: 10.1029/2012gc004152
|View full text |Cite
|
Sign up to set email alerts
|

Rapid surficial oxidation of synthetic Fe‐Ti oxides at high temperature: Observations and consequences for magnetic measurements

Abstract: [1] Synthetic polycrystalline samples of Fe-Ti oxides (titanomagnetite, Tmt ss ; ilmenite-hematite ss , Ilm ss ; pseudobrookite ss , Psb ss ) are very sensitive to changes in the redox conditions at high temperatures, either during synthesis experiments or during thermomagnetic measurements. For instance, exposure to air for a few seconds at the end of a synthesis run at 1300 C of a Tmt ss -Ilm ss sample produces surficial oxidation down to a depth of some 100 mm. This oxidation zone is well visible on backsca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Oxidation exsolution (oxyexsolution) of titanomagnetites irreversibly increases T C [e.g., Lattard et al, 2012] by transforming a single-phase cubic oxide into intergrowths of an Fe-rich cubic end-member (with a higher T c ) and a Ti-rich rhombohedral end-member (typically paramagnetic at room temperature). In our samples it occurs very slowly in the 300 C-425 C annealing experiments, gradually transforming the singlephase titanomagnetites.…”
Section: Oxyexsolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxidation exsolution (oxyexsolution) of titanomagnetites irreversibly increases T C [e.g., Lattard et al, 2012] by transforming a single-phase cubic oxide into intergrowths of an Fe-rich cubic end-member (with a higher T c ) and a Ti-rich rhombohedral end-member (typically paramagnetic at room temperature). In our samples it occurs very slowly in the 300 C-425 C annealing experiments, gradually transforming the singlephase titanomagnetites.…”
Section: Oxyexsolutionmentioning
confidence: 99%
“…Cumulative heating times approaching 9000 h in this moderate temperature range have an effect comparable to that of a single 5 h treatment at 650 C (Figure 7c). High degrees of oxyexsolution (as observed to occur naturally in site MSH003) typically require heating in air for several hours at 600 C-700 C or for a few seconds at 1000 C-1300 C [Lattard et al, 2012]. Geochemistry, Geophysics, Geosystems…”
Section: Oxyexsolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, in principle, the cation distribution varies with temperature and at high-temperature cation ordering is randomized, the cation distribution is complicated by its dependence on time, temperature, and thermodynamic stability due to oxygen fugacity, composition, and cation site occupancy (e.g., Sauerzapf et al 2008;Lattard et al 2012;Bowles et al 2013). Despite these uncertainties, Bowles et al (2013) have shown that T C of homogeneous titanomagnetite in pyroclastic flows is strongly influenced by the thermal history around the T C for Ti, Mg, and Al-bearing titanomagnetite.…”
Section: Introductionmentioning
confidence: 99%
“…Although our samples do not contain significant amount of Ti, titanomagnetite solid solution deserves to be mentioned as it is the most well‐established solid solution in the spinel prism. For different degrees of cation ordering, there is little variation in T c for titanomagnetite solid solution series (e.g., Lattard et al, 2012; Moskowitz, 1987). On the contrary, variation in T c is rather high for magnetite‐spinel solid solution (Harrison & Putnis, 1996).…”
Section: Discussionmentioning
confidence: 99%